2020
DOI: 10.3390/app10103447
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Green Extraction of Polyphenolic Antioxidants from Salvia fruticosa Using Cyclodextrins: Optimization, Kinetics, and Composition

Abstract: S. fruticosa, collectively known as Cretan sage, is a medicinal plant to which a number of bioactivities have been attributed. In spite of its importance in nutrition and pharmacy, reports on the extraction of major polyphenols using sustainable processes are particularly limited. In this study, three common cyclodextrins, namely, methyl β-cyclodextrin (m-β-CD), hydroxypropyl β-cyclodextrin (HP-β-CD), and β-cyclodextrin (β-CD), were tested as green boosters of aqueous extraction of polyphenols from aerial part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 30 publications
1
14
1
Order By: Relevance
“…However, no statistical difference was seen compared to the Y TP achieved at the other pH tested. This is in contrast to recent studies on the importance of the pH in the HP-β-CD-aided extraction of polyphenols [15,16], where pH effects on polyphenol extraction performance was found to be significant. Optimum pH value for HP-β-CD-aided extraction of S. fruticosa polyphenols was shown to be 3.90 [16], very close to pH 4 determined in this study.…”
Section: The Effect Of Ph Regulationcontrasting
confidence: 99%
See 1 more Smart Citation
“…However, no statistical difference was seen compared to the Y TP achieved at the other pH tested. This is in contrast to recent studies on the importance of the pH in the HP-β-CD-aided extraction of polyphenols [15,16], where pH effects on polyphenol extraction performance was found to be significant. Optimum pH value for HP-β-CD-aided extraction of S. fruticosa polyphenols was shown to be 3.90 [16], very close to pH 4 determined in this study.…”
Section: The Effect Of Ph Regulationcontrasting
confidence: 99%
“…Construction of the predictive model was performed by deploying a response surface methodology via a Box-Behnken design with three central points. The basis for choosing the process variables was literature data [15,16] illustrating their profound influence on the extraction yield in total polyphenols (Y TP ), which was the response. The actual and codified levels of the variables are analytically presented in Table 1.…”
Section: Experimental Design and Response Surface Optimizationmentioning
confidence: 99%
“…For the screening process, all DES were tested as 70% (w/v) aqueous mixtures. Control solvents were 60% (v/v) ethanol, 60% (v/v) methanol and deionized water [14,16]. Extractions were accomplished in a 20-mL glass vial, using 15 mL of each solvent and 0.375 g of plant material, for 150 min.…”
Section: Batch Stirred-tank Extraction Processmentioning
confidence: 99%
“…Previous studies on the extraction of polyphenols from S. fruticosa using methyl β-cyclodextrin (m-β-CD) showed that extracts with increased polyphenol concentration and improved antioxidant characteristics could be obtained at 80 • C [14]. However, a following investigation with a 60% (w/v) hydroglycerolic mixture demonstrated that Y TP displayed a gradual decrease when extraction temperature varied from 50 to 80 • C [42], although differences were non-significant (p < 0.05).…”
Section: Extraction Kinetics-temperature Effectsmentioning
confidence: 99%
See 1 more Smart Citation